2018
DOI: 10.1128/jvi.01018-18
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs Potently Inhibit the Replication of Zika Viruses by Inducing the Degradation of AXL

Abstract: Zika virus (ZIKV) is genetically and biologically related to other Flaviviridae family members and has disseminated to many countries. It is associated with severe consequences including the abnormal development of the neural system in fetuses and neurological diseases in adults. Therefore, developing anti-ZIKV drugs is of paramount importance. Screening of generic drugs revealed that several non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin, ibuprofen, naproxen, acetaminophen, and lornoxicam p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…The ORF8 S mutant expressing plasmid was constructed via a PCR-based mutagenesis method from pcDNA3.1-ORF8-HA by introducing a point mutation (L to S) at the 84 amino acid. The green fluorescent protein (gfp) coding sequence was at the 3’ terminus and constructed into the pcDNA3.1 vector 47 . The IRES-GFP sequence was inserted into 3’ ORF8-HA and named ORF8-GFP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORF8 S mutant expressing plasmid was constructed via a PCR-based mutagenesis method from pcDNA3.1-ORF8-HA by introducing a point mutation (L to S) at the 84 amino acid. The green fluorescent protein (gfp) coding sequence was at the 3’ terminus and constructed into the pcDNA3.1 vector 47 . The IRES-GFP sequence was inserted into 3’ ORF8-HA and named ORF8-GFP.…”
Section: Methodsmentioning
confidence: 99%
“…Co-IP assay were performed as our previously described 47 . In brief, HEK293T cells were lysed with NP40 lysis buffer (10 mM Tris-HCl, pH 7.4, 150 mM NaCl, 0.5% NP-40, 1% Triton X-100, 10% glycerol, 2 Mm EDTA, 1 mM Na3VO4, 1% protease inhibitor cocktail (Sigma-Aldrich) and phosphatase inhibitor cocktail (TOPSCIENCE) for 30 min on ice with briefly vertaxing every 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the antiviral activity against SARS-CoV-2 virus demonstrated here, naproxen also exhibited antiviral properties in cellular and rodent models of Influenza A and B 6,10,26 . Naproxen also inhibited the replication of the unrelated Zika virus 27 . Therefore, from three unrelated single-stranded RNA virus, we suggest that naproxen could present broad-spectrum antiviral properties.…”
Section: Naproxen Inhibits Sars-cov-2 Infection In Veroe6 Cells and Imentioning
confidence: 97%
“…Zika virus titers were determined by a plaque assay performed on Vero cells by following the procedures as described previously [10]. Briefly, Vero cells were seeded in 12 well plates and used for infection when the cells were grown to 90% confluence.…”
Section: Zikv Titration and Plaque Assaymentioning
confidence: 99%
“…However, many ISGs are still undiscovered, and their antiviral mechanisms need to be further investigated and thoroughly characterized. Recent studies have indicated that several ISGs, such as IFITM1 [9], IFITM3 [9], PARP12 [10] and Viperin [11] could inhibit ZIKV replication. A recent high-throughput cDNA library derived from type I IFN-treated human cells screen was used to identify a set of genes that form a novel regulatory network of host factors that mediates antiviral effects [12,13].…”
Section: Introductionmentioning
confidence: 99%